Women Representation as Symbols of Mother Nature: An Ecofeminism Perspective in Moana Film - Mohd Hanafi Jumrah; Haryati Abdul Karim (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2022)
Women are often considered weak and discriminated against, so women rise through the wave of feminism. Ecofeminism is one of the social thoughts and movements that connect women and ecology in facing environmental challenges. This study investigates the relationship between women and nature featured in Moana (2016) film from ecofeminist thinking. The study also wanted to examine women’s relationships with ecological issues featured in the same film. This study would look at the relationship between women and nature featured in Moana (2016) film from an ecofeminist perspective and semiotic. The study also wanted to examine relationships between women’s ecological issues in the film. The emergence of ecofeminism shows the relationship between women with nature and animals. This study uses a qualitative method which is a textual analysis of the movie in six frames. These frames were selected based on several elements from the miseenscene. Once the frames are selected, the frames will be analyzed and form the themes and categories. The results found that women’s relevance to these ecological issues is divided into three based on the framework of interpretation of the ecological revolution namely ecology, reproduction, and consciousness, women in the film Moana (2016) are often associated with nature through two ecofeminism thoughts: natural ecofeminism and spiritual ecofeminism. In addition, this study also found that women's association with ecological issues is divided into two based on the framework of interpretation of the environmental revolution, namely ecology and reproduction. This study also shows that female characters in Moana (2016) films are more dominant, showing gender equality.